1988
DOI: 10.1007/bf00254382
|View full text |Cite
|
Sign up to set email alerts
|

Results of a double blind study of 89-strontium therapy of skeletal metastases of prostatic carcinoma

Abstract: Forty-nine patients were treated with either 3 x 75 MBq 89Sr or saline as placebo. Analysis of results 1 to 3 years after therapy revealed the ineffectiveness of 89Sr to relieve pain from metastases. Unexpectedly, a higher survival rate was found after Sr application (46% vs 4% after 2 years). Covariate analysis underlines the effect of 89Sr therapy on life expectation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 6 publications
0
24
1
1
Order By: Relevance
“…Radionuclide therapy does not suffer from this limitation and represents an attractive option. In patients treated with radiolabelled MAbs or bone-seeking tracers (strontium-89, rhenium-186 diphosphonate) the red marrow often is the critical tissue in terms of dose-limiting toxicity [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Radionuclide therapy does not suffer from this limitation and represents an attractive option. In patients treated with radiolabelled MAbs or bone-seeking tracers (strontium-89, rhenium-186 diphosphonate) the red marrow often is the critical tissue in terms of dose-limiting toxicity [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Of these 31 studies, 6 reported on bone metastases from breast cancer, [71][72][73][74][75][76] 13 reported on bone metastases from prostate cancer [77][78][79][80][81][82][83][84][85][86][87][88][89] and 12 reported on bone metastases from OSTs. [90][91][92][93][94][95][96][97][98][99][100][101] Of the remaining eight studies that did contribute data to the network meta-analyses, four reported breast cancer 31,[102][103][104] [18 reports 22,31,[102][103][104][105][106][107][108][109][110][111][112][113][11...…”
Section: Number and Type Of Studies Includedmentioning
confidence: 99%
“…As Metastron is a pure ß-emitter, it therefore stands to reason that a considerable amount of the tumour may in fact be underirradiated by the use of a single injection. Arguments for the use of Metastron in multiple therapies, as has been performed by Buchali et al [29] and Tenvall et al [31], may thus be valid. Recogni tion of the factors underlying the radiobiological response to radiation has also been increasing, particularly regard ing radiation at ultra-low dose rates.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…In the Trans Canada study, the median survival was 34 weeks in patients receiving placebo [27], A treatment that will extend quality-assured survival in this population is, therefore, much needed. Buchali et al [29] evaluated 49 patients after treatment with either Metastron, at a dose of 2 mCi monthly for 3 months, or a saline placebo. A statistically significant prolongation of survival was seen in the group receiving Metastron.…”
Section: Survivalmentioning
confidence: 99%